Development of Monoclonal Antibody to Specifically Recognize VP0 but Not VP4 and VP2 of Foot-and-Mouth Disease Virus - Sun Young Park; Jong Sook Jin; Dohyun Kim; Jae Young Kim; Sang Hyun Park; Jong-Hyeon Park; Choi-Kyu Park; Young-Joon Ko (Pathogens, 2022)
Foot-and-mouth disease (FMD) is a highly contagious vesicular disease that affects cloven-hoofed animals and often causes enormous economic loss in the livestock industry. The capsid of FMD virus (FMDV) consists of four structural proteins. Initially, one copy each of the proteins VP0, VP3, and VP1 are folded together into a protomer, and five copies of the protomer compose a pentamer. Finally, 12 pentamers are assembled into an icosahedral capsid. At the maturation stage during RNA encapsidation, VP0 is cleaved into VP4 and VP2. The mechanism underlying VP0 maturation remains unclear. While monoclonal antibodies (mAbs) against VP2 have been developed in previous studies, a mAb specific to VP0 has not yet been reported. In this study, we generated VP0-specific mAbs by immunizing mice with peptides spanning the C-terminal amino acids of VP4 and N-terminal amino acids of VP2. We verified that these mAbs displayed specificity to VP0 with no reactivity to VP4 or VP2. Therefore, these mAbs could prove useful in identifying the role of VP0 in FMDV replication and elucidating the mechanism underlying VP0 cleavage into VP4 and VP2.